Electronic Cigarette Cessation among Adolescents and Young Adults. (8th September 2021) - Garey, Lorra; Scott-Sheldon, Lori A. J.; Olofsson, Hannah; Nelson, Kimberly M.; Japuntich, Sandra J.
Abstract: Background: E-cigarette use is common among adolescents and young adults, yet little is known about e-cigarette cessation among this group. The current study assessed e-cigarette cessation attempts, interest in e-cigarette cessation, and methods of e-cigarette cessation most favored by young e-cigarette users. Methods: A cross-sectional survey was administered via Facebook and Instagram between February and April 2019 to enroll current, regular e-cigarette using adolescents and young adults who reported non-regular use of other tobacco products. Participants included 212 (51.4% female) adolescents and young adults (14 to 21  years of age) who reported six or more days of e-cigarette use and less than four days of other tobacco product use in the last 30  days. Results: More than half ( n   =  110; 51.9%) of the participants reported at least one past serious e-cigarette quit attempt. Among those, the average number of past quit attempts was 2.9 ( SD  = 3.9). Of the 157 (74.1%) participants who indicated they were interested in quitting e-cigarettes, 78 (49.7%) endorsed health risks as their primary reason for wanting to quit e-cigarettes. The most frequently endorsed intervention methods to aid in e-cigarette cessation were those delivered via digital methods, such as smartphone apps. Conclusion: The current study provides preliminary data to support continued development of e-cigarette cessation treatments for adolescents and young adults. Future research should evaluate the potential use of digital methods to aid in e-cigarette cessation.